2009
DOI: 10.2105/ajph.2008.147827
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Alcohol Use and Violent Behavior Among Urban African American Youths From Adolescence to Emerging Adulthood: A Longitudinal Study

Abstract: Objectives-We examined the developmental trajectories of alcohol use and violent behavior and the longitudinal relationship between these behaviors from adolescence to emerging adulthood.Methods-Our sample includes 649 African-American youths (49% male) followed for 8 years. Violent behavior and alcohol use were measured by asking youths the frequency of each behavior in the past 12 months using pencil-and-paper questionnaires. Growth curve analyses were conducted to identify the developmental trajectories of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 28 publications
5
47
0
8
Order By: Relevance
“…Studies show that adolescent drinkers are more likely to participate in violent behavior and other types of crime in adulthood (e.g., theft, damage to property) compared with nondrinking adolescents (Anderson et al, 1999;Duncan et al, 1997;Swahn et al, 2004). Xue et al (2009), for example, found signifi cant associations between trajectories of adolescent alcohol use and trajectories of violence over 8 years in an African American sample, even after controlling for shared risk factors. In addition, Ellickson et al (2003) found that in early adulthood (age 23), early adolescent drinkers had twice the likelihood of being arrested and engaging in predatory violence, stealing, and committing a felony, compared with nondrinkers.…”
Section: Adolescent Drinking and Later Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that adolescent drinkers are more likely to participate in violent behavior and other types of crime in adulthood (e.g., theft, damage to property) compared with nondrinking adolescents (Anderson et al, 1999;Duncan et al, 1997;Swahn et al, 2004). Xue et al (2009), for example, found signifi cant associations between trajectories of adolescent alcohol use and trajectories of violence over 8 years in an African American sample, even after controlling for shared risk factors. In addition, Ellickson et al (2003) found that in early adulthood (age 23), early adolescent drinkers had twice the likelihood of being arrested and engaging in predatory violence, stealing, and committing a felony, compared with nondrinkers.…”
Section: Adolescent Drinking and Later Violencementioning
confidence: 99%
“…As described by Jessor and Jessor's problem-behavior theory (1977), shared predisposing risk factors serve to facilitate and perpetuate various forms of deviance, including both alcohol use and violent behaviors. Such shared risk factors include socioeco-nomic status, family characteristics and functioning, personal characteristics, measures of behavior problems and delinquency, academic achievement, and other drug use (Hicks et al, 2010;Swahn and Donovan, 2006;Wells et al, 2004;White et al, 1999;Xue et al, 2009). Although much of the relationship between various forms of deviance seems to be attributable to shared causes, evidence suggests that shared risk factors only partially explain the relationship between alcohol and violence (Osgood, 1998).…”
Section: Adolescent Drinking and Later Violencementioning
confidence: 99%
“…This result is consistent with a second hypothesis of this study. According to Xue, Zimmerman and Cunnighham (2009), aggressive behavior increases in middle to late adolescence and declines in emerging adulthood. Studies also have shown that physical aggression decreases but indirect aggression increases from childhood to adolescence (Barker, Tremblay, Nagin, Vitaro, & Lacourse, 2006;Campbell et al, 2010;Cote, Vaillancourt, Barker, Nagin & Tremblay, 2007;Underwood, Beron & Rosen, 2009;Vaillancourt, Miller, Fagbemi, Cote, & Tremblay, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…12,62 Weapon carriage during the past six-months was measured via two items assessing whether participants "carried a knife or razor" and/or "carried a gun." 63 Current gang affiliation was assessed via a question from the Tulane National Youth Study. 48 Community violence exposure was measured with five items, 64 with higher scores indicating more frequent community violence exposure.…”
Section: Methodsmentioning
confidence: 99%